Quantifying the Crews: Seafaring Labour at Swansea, 1838–1903. (1st December 2013) - Haines, Richard
This article examines the changing character of seafaring labour at Swansea during the nineteenth and early twentieth centuries. In particular, it demonstrates how the predominantly local labour market of the early nineteenth century was replaced from the 1850s by the increasing prominence of seamen from west Wales and, later, the wholesale employment of foreigners. The factors accounting for these shifts are examined in depth, including the relative attraction of seafaring as an occupation and changing demands among local shipowners. The research is based on a systematic analysis of crew agreement lists, sources that have received comparatively little attention from historians. As such, this article not only establishes new agendas for maritime labour history, but also contributes to existing social, cultural and urban history scholarship.